Inflammation imaging of atherosclerosis in Apo-E-deficient mice using a (99m)Tc-labeled dual-domain cytokine ligand - Liu, Zhonglin (2014)
Interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) play a critical role in initiating and accelerating atherosclerosis. This study evaluated the imaging properties of (99m)Tc-TNFR2-Fc-IL-1RA ((99m)Tc-TFI), a dual-domain cytokine radioligand that targets TNF-α and IL-1β pathways, in assessing atherosclerosis development in apolipoprotein-E-deficient (ApoE(−)/(−)) mice. METHODS: The feasibility and specificity of detecting atherosclerosis with (99m)Tc-TFI SPECT imaging were investigated in ApoE(−)/(−) and ApoE(+)/(+) mice. Fifty-four ApoE(−)/(−) mice were fed either an atherogenic diet (AGD) or a normal diet (ND) beginning at 5 weeks of age. Eighteen Apo-E wild-type (ApoE(+)/(+)) mice were fed a ND. Two groups of ApoE(−)/(−) mice (n=12 each group) on AGD and ND were imaged three times with (99m)Tc-TFI and a high-resolution SPECT system at 20–25, 30–40, and 48–52 weeks to study the evolution of atherosclerotic plaque. RESULTS: Focal radioactive accumulations in the aortic arch region were observed in the ApoE(−)/(−) mice (n=12) on AGD but not in the ApoE(+)/(+) mice on ND (n=10). Apo-E(−)/(−) mice on ND (n=11) exhibited lower radioactive uptake than ApoE(−)/(−) mice on AGD (P<0.05). Co-injection of an excess of cold ligand with (99m)Tc-TFI resulted in significant reduction of (99m)Tc-TFI uptake in the ApoE(−)/(−) mice on AGD. Longitudinal studies showed that (99m)Tc-TFI uptake in the aortas of ApoE(−)/(−) mice progressively increased from 20 to 48 weeks. Real-time PCR assays demonstrated that atherosclerotic aortas expressed significantly higher IL-1β and TNF-α than the aortas from wild-type controls. CONCLUSIONS: Atherosclerotic plaques were detected by (99m)Tc-TFI imaging in ApoE(−)/(−) mice. (99m)Tc-TFI is promising for specific detection of inflammatory response in atherosclerotic plaques.